Precipitação interna de árvores esparsas em área urbana - GUILHERME SANTANA SILVA (2022)
The throughfall is an important part of the hydrological cycle. In this context, isolated trees are able to intercept significant amounts of water, with the potential to alleviate urban drainage systems. The objective is to detail the internal precipitation process in isolated trees commonly found in cities located at Cerrado Biome. This research had field experiments with tree species recurrent in urban afforestation in the Cerrado, the individuals studied are located on the Campus of the Federal University of Mato Grosso do Sul, in Campo Grande – MS. For this, twelve arboreal individuals were monitored, using millimeter rain gauges to measure the amount of throughfall and the total precipitation at site. The twelve tree individuals are of the following species: 2 Tabebuia roseoalba, 3 Handroanthus impetiginosus, Apeiba tibourbou, 1 Genipa americana, 1 Ficus benjamina, 1 Licania tomentosa, 1 Aspidosperma tomentosum, 1 Dimorphandra mollis and 1 one from the Terminalia family. The observations show that there is a correlation between the projected canopy area and internal precipitation, being Oiti, Lincaia tomentosa with the lowest throughfall value – 11,25 mm/day - and Ipê-rosa, with the highest througfall value - 18,25 mm/day.229. Concluded that the dendrometric characteristics directly influence the interception of rainwater, being necessary more studies to better correlate the characteristics of the trees and the interception capacity